Chapter 9 Digital Samhandling in Education for the Unforeseen Future - Hammer Furnes, Gila (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2018)
"This chapter aims to discuss whether digital interaction (samhandling) in education requires a new pedagogy, which, to a greater extent than before, takes into account risks and unforeseen events. The major focus is on digital samhandling between teachers and students. Future education should prepare students for a world in which samhandling between individuals is predicted to be increasingly digital. At the same time, teachers currently refrain from using digital tools in order to interact pedagogically with students. A "mixed methods" survey of 96 randomly-chosen schoolteachers in primary and secondary schools in Norway shows that the respondents give various reasons for using Learning Management Systems (LMS) to a greater extent for administrative purposes than for pedagogical ones. The main obstacle is that teachers do not know exactly how digital samhandling should be facilitated educationally and what the consequences may be for the students and education in general. The conclusion is that the future is unknown, and the unforeseen is partly learned through teachers' professional judgment. Therefore, "new" pedagogy need not necessarily consist of more educational models and theories of "what works." Perhaps the "new" pedagogy should be, to a greater extent, based on samhandling literacy and problem-based learning?"